Pengaruh Tangible Asset Terhadap Struktur Modal Dengan Nilai Perusahaan Sebagai Variabel Moderating Pada Subsektor Otomotif Yang Terdaftar di BEI - Sahya, Aqilla Fadia; Ardiana, Meta (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
This research aims to determine the effect of tangible assets on capital structure with company value as a moderating variable in the automotive subsector listed on the BEI in 2019-2022. Sample selection was carried out using a purposive sampling method, so that 12 companies were obtained that met the criteria with 4 years of observation. The data used is secondary data originating from the company's annual report, while data analysis uses the SmartPLS software method. The results of this research show that tangible assets have no effect on capital structure. Apart from that, company value is unable to moderate the influence of tangible assets on capital structure.Keywords: Analysis; Internal Control System of Accounts Receivable